A subversão de gênero nos diários de Alejandra Pizarnik - Silva, Erlândia Ribeiro da (2024)
This thesis examines how Alejandra Pizarnik (1936-1972) constructs her gender identity and sexuality through performance in her Diaries from the period 1954 to 1960. Drawing on Judith Butler's theory of performativity in Gender Trouble: Feminism and the Subversion of Identity, it argues that Pizarnik resists being confined to a fixed identity. She subverts both the predefined heteronormative gender expectations for women of her time, as imposed by patriarchal society, and the emergent feminist movement's emphasis on a unified female identity. While patriarchal norms portrayed women as fragile and submissive, the early feminist movement also risked essentializing femininity, thus confining individuals to pre-established categories rather than promoting freedom. Through Butler's lens, this thesis explores how Pizarnik's voice in the Diaries negotiates and subverts patriarchal norms, carving out spaces for singularity and potentially leading to the creation of new forms of identity. Ultimately, it concludes that the rigid enforcement of gender categories by patriarchal power structures fosters a sense of melancholy.